One-pot Au [III]-/lewis acid catalyzed cycloisomerization of nitroalkynes and [3+3]cycloaddition with donor-acceptor cyclopropanes - Dhote, Pawan S.; Ramana, V. Chepuri (Organic Letters, 2019)
A one-pot protocol for the synthesis of a tricyclic pseudoindoxyl scaffold from 2-nitroalkynylbenzenes, comprising of an Au(III)-catalyzed nitroalkyne cycloisomerization leading to isatogen and its [3 + 3]-cycloaddition with donor-acceptor cyclopropanes mediated by a suitable Lewis acid, has been developed.

Oxidative rearrangement of stilbenes to 2,2-diaryl-2-hydroxyacetaldehydes - Kalshetti, Rupali G.; Ramana, V. Chepuri (ACS Omega, 2020)
A one-pot oxone-mediated/iodine-catalyzed oxidative rearrangement of stilbenes leading to 2,2-diary1-2-hydroxyacetaldehydes is described. Control experiments revealed that a 2,2-diarylacetaldehyde was initially formed that undergoes subsequent alpha-hydroxylation. The resulting alpha-hydroxyaldehydes have been subjected to a one-pot Still Gennari olefination followed by cyclization, leading to S,S-diaryl-y-butenolides.

Ru-catalyzed asymmetric transfer hydrogenation of alpha-acyl butyrolactone via dynamic kinetic resolution: asymmetric synthesis of bis-THF alcohol intermediate of darunavir - More, V. Ganesh; Malekar, V. Pushpa; Kalshetti, Rupali G.; Shinde, Mahesh H.; Ramana, V. Chepuri (Tetrahedron Letters, 2021)
The Ru-catalyzed enantio- and diastereoselective dynamic kinetic resolution of alpha-(benzyloxy/benzoyloxy)acyl-gamma-butyrolactones has been examined via transfer hydrogenation. Employing the in situ prepared (R,R)-Ru-FsDPEN catalyst, the transfer hydrogenation of using formic acid/triethylamine at rt gave the corresponding (S)-3-((S)-2-(benzyloxy/benzoyloxy)-1-hydroxyethyl)dihydrofuran-2(3H)-on e with good to excellent diastereo- and enantioselectivity. One of the resulting hydrogenation product prepared on gram scales was utilized for the synthesis of (3R,3aS,6aR)-hexahydrofuro[2,3-b]furan-3-ol (1), a key synthetic intermediate of various HIV protease inhibitors such as darunavir with excellent enantio-(95% ee) and diastereoselectivities (dr 95:5). (C) 2021 Elsevier Ltd. All rights reserved.
Keywords: Bis-THF-OH intermediate; Darunavir; Dynamic kinetic resolution; Ru-catalysis; transfer hydrogenation

Synthesis of anisotropic rod-like gold nanostructures in organic media (vol 133, 106, 2021) - Prasad, V. Bhagavatula L.; Sivasankaran, Prathap Chandran; Patel, Pitambar; Malekar, V. Pushpa; Maya, V. K.; Ramana, V. Chepuri (Journal of Chemical Sciences, 2021)

Competing intra- vs intermolecular nitrene transfer in the [Au]-catalysed reaction of 2-alkynylphenylazides - Dhote, Pawan S.; Ramana, V. Chepuri (Advanced Synthesis & Catalysis, 2022)
The possibility of interrupting the gold-catalysed intramolecular cyclization of 2-alkynylphenylazide derivatives, employing known nitrene transfer reagents such as anthranil and its isomer 1,2-benzisoxazole, has been attempted in search of developing simple tools for product diversification. With 1,2-benzisoxazoles, the intermolecular nitrene transfer leading to quinazoline is competitive with intramolecular azidoalkyne cyclization resulting in spiro indol-3-ylidene derivatives. However, in case of the reaction in the presence of anthranil, both intra- and intermolecular nitrene transfer processes result in the same product indol-3-ylidene.
Keywords: 2-Benzisoxazole; Anthranil and 1; Gold catalysis; Nitrene Transfer; Quinazoline

Facile synthesis of the spiro-pyridoindolone scaffold via a gold-catalysed intramolecular alkynol cyclisation/hydroindolylation - Shinde, Mahesh H.; Ramana, V. Chepuri (Organic & Biomolecular Chemistry, 2022)
A simple approach for the synthesis of pyridoindolone scaffolds with a spiroannulated tetrahydrofuran ring is described. The overall process comprises intramolecular sequential gold-catalysed 5-endo-dig alkynol cycloisomerization and subsequent addition of indole C2 to the in situ generated oxocarbenium cation.

Rediscovering Bacon's hydrazine/phenylhydrazine mediated cyclization of 2,2 `-dicarbonylbi(hetero)aryls: construction of (5-azo)-/indazolo[2,3-a]quinolines - Dhote, Pawan S.; Ramana, V. Chepuri (Organic & Biomolecular Chemistry, 2022)
Hydrazine/phenylhydrazine-mediated reductive dicarbonyl coupling reactions have been carried out under mild conditions to provide polycyclic aromatic compounds and azo-substituted polyaromatic compounds. This method has a broad substrate scope with good functional group compatibility.

Synthesis of central spiro-bis-THF fragments of symbiospirols A-C - Shinde, Mahesh H.; Kona, Chandrababu N.; Ramana, V. Chepuri (New Journal of Chemistry, 2022)
The gold catalysed alkynediol spiroketalization to assemble the central spiro-bis-THF fragments (C22-C33 and C36-C47) of symbiospirols A-C is documented. The adopted chiral pool approach employed commercially available d-glucose and l-malic acid in the synthesis of key building blocks. In addition, two other possible diastereomers have been synthesized in order to establish the relative stereochemistry of the unassigned THF-center of symbiospirols B/C.

Ru-catalyzed asymmetric transfer hydrogenation of racemic /3-keto γ-lactams via dynamic kinetic resolution - Malekar, V. Pushpa; More, V. Ganesh; Ramana, V. Chepuri (Tetrahedron, 2024)
The enantioselective transfer hydrogenation of racemic /3-keto gamma-lactams via dynamic kinetic resolution using a chiral Ru(II) catalyst has been developed for the synthesis of optically active /3-hydroxyl lactams with excellent conversion (up to 99 %), high diastereomeric ratio (dr dr 93:07) and enantiomeric selectivity (89 % ee ). The reaction proceeded by using HCO2H/Et3N 2 H/Et 3 N as hydrogen donor and features mild, additive free reaction conditions, fast crystallization, broad substrate scope, and an operationally simpler setup than that for molecular hydrogenation.
Keywords: (R)-1-((R)-Pyrrolidin-3-yl)ethan-1-ol; /3-keto gamma-lactams; Asymmetric transfer hydrogenation; Dynamic kinetic resolution; Fluroquinolone antibiotics

Design and synthesis of C-α-D-mannopyranoside linked mesoporous silica nanoparticles - Nechooli, Hemanth K.; Ramtenki, Vilas; Kumar, Chepuri V. Suneel; Prasad, V. B. L.; Ramana, V. Chepuri (Journal of Chemical Sciences, 2025)
Mannose functionalized mesoporous silica nanoparticles (MSNs) offer a promising approach for developing more targeted, effective, and safer cancer therapies. For many of the applications, immobilization of carbohydrates like mannose onto MSNs is a crucial aspect, and in most cases, mannose moieties are connected through O-glycosidic linkages that are susceptible to acidic/enzymatic hydrolysis. To generate a stable mannose-functionalized MSN, we designed a novel C(14)-alpha-mannosylated tetradeca-1-yne. The key steps involved in the synthesis of C-mannosylated alkyne are C1-alkynylation of tri-O-acetyl-D-glucal with 1-trimethylsilyl-tetradec-1-yne, followed by stereoselective dihydroxylation and the isomerization of the internal triple bond to a terminal position. This mannose ligand was then immobilized onto azidopropyl-functionalized SBA-15 through the Cu(I)-catalyzed azide-alkyne click (CuAAC) reaction. Various physical techniques such as low-angle powder XRD, N-2 adsorption isotherms (BET), Fourier transform infrared (FTIR), high-resolution transmission electron microscopy (HRTEM), field emission scanning electron microscopy (FE-SEM), and thermogravimetric analysis (TGA) have been employed to characterize this C-mannosyl SBA-15 silica matrix. We evaluated the binding ability of C-mannosyl SBA-15 nanoparticles by using fluorescein-labelled Con-A as a target protein.
Keywords: C-mannoside; Click reaction; mannose specific proteins; Mesoporous silica nanoparticles; Zipper reaction